The Impact of Climate Change on the Security of Christians - Tahyné Kovács Ágnes (Budapest-jelentés a keresztényüldözésről, 2024)
The protection of the created world is increasingly coming to the forefront for believers in the form of environmentally conscious lifestyles and ethical considerations, with many Christian leaders emphasizing the importance of combating climate change, addressing it as a moral duty in Church documents. At the same time, the fate of persecuted Christians, especially in climate-affected areas, is becoming increasingly difficult. In Iran, Afghanistan, Nicaragua, Nigeria, Somalia, and other countries, personal persecution and organized attacks are being used to prevent Christians from living peacefully together with people of other faiths. In a dynamically changing environment, the connections between climate change and the persecution of Christians are the sum of a number of factors, some of which are highlighted below to illustrate the context. Climate change is increasingly recognised as a risk multiplier and driver of atrocities, with an estimated 40-60% of civil wars triggered by conflicts over natural resources over the past 60 years.